Measurement of 222Rn in ground water and NORMs in top soil in the environs of Rooppur Nuclear Power Plant site and associated health hazard - Pervin, Shikha; Banik, Subrata; Sultana, Nazneen; Karmaker, Shanjib; Khandaker, Mayeen Uddin *; Yeasmin, Selina; Uddin, Md Mohi (Springer, 2024)
This study determines the prevailing concentrations of 222Rn in twenty groundwater samples and primordial radionuclides in twelve soil samples collected from the surrounding area of the Rooppur Nuclear Power Plant (RNPP) in Bangladesh. The mean concentration of 222Rn, 226Ra, 232Th and 40K in the studied samples was found to be 4.42 ± 2 Bq/L (Water), 25.2 ± 5.3, 23.9 ± 6.3 and 317.1 ± 31.4 Bq kg−1 (Soil) respectively. Associated health hazards were estimated and compared with the respective safety limits recommended by international organizations. The present results may serve as the base values of naturally occurring radioactive materials in the vicinity of the RNPP in Bangladesh.